Boundary transformation in a school-university teacher education partnership: the potential of developmental work research in DETAIL - Ellis, V (2008)
This paper explores the potential of a variation of the Developmental Work Research methodology (DWR) in the 'expansive learning' (Engeström 1991, 1999) of teacher educators within an influential school-university teacher education partnership in the UK. A hybrid research-development project (Developing English Teaching and Internship Learning - DETAIL) has aimed to reconfigure the partnership between the university and schools at a systemic level through the introduction of two new pedagogic tools and to focus on contradictions in exiting 'standard' practice as creative disturbances likely to be generative of positive change and development. The paper argues that the project's methodological framework - DWR and the concept of 'Change Laboratories' (Engeström 1999, 2007) - offers a powerful means of both understanding and working on the processes of change. It can achieve this by refocusing analysis culturally and historically at the systemic rather than the individual level and by using the tools of Activity Theory in a participatory way to support the learning of the 'change agents'. The paper highlights two instances from the DWR process to show how the introduction of the pedagogic tools - collaborative professional inquiry and collaborative planning and teaching - mediated participants' work on the object of activity. The paper emphasises the complexity of the change processes at work whilst demonstrating the methodology's potential to transform boundaries within and between activity systems.